Determination of vertical displacements of infrastructure objects based on the radar interferometry data - Pakshyn, Maksym; Liaska, Ivan; Dorosh, Liubov; Grytsyuk, Tetyana; Gera, Oksana (Geodesy and Cartography, 2022)
The aim of this paper is to determine the current capabilities of the radar interferometry methods and the expediency of their use for observations of the infrastructure vertical deformations on the example of the educational building of Ivano-Frankivsk National Technical University of Oil and Gas. Based on the obtained radar information, we were able to process an array of data for a short period using the method of Persistent Scatterers Interferometry (PS) (interferometry of constant reflectors of the radar signal). As a result, we determined the average velocity values of the vertical displacements of the university area. In order to establish the reliability of the results obtained by radar interferometry, the values of the structure displacements were measured according to the permanent station FRKV data, which operates in the IFNTUOG educational building №5. The results, based on both GNSS and radar interferometry methods, correlate and confirm the absence of significant deformation shifts of the construction.